Neighborhoods and adolescent polysubstance use in Jamaica - Amrita Gill; Erica Felker-Kantor; Colette Cunningham-Myrie; Lisa-Gaye Greene; Parris Lyew-Ayee; Uki Atkinson; Wendel Abel; Simon G. Anderson; Katherine P. Theall (PeerJ, 2023)
Background The purpose of this study was to identify latent classes of polysubstance use among adolescents in Jamaica and the role of neighborhood factors in the association with polysubstance use class membership. Methods This secondary analysis utilized a national cross-sectional household drug use survey conducted across 357 households in Jamaica (April 2016–July 2016) among a total of 4,625 individuals. A total of 750 adolescents (11–17 years) were included in this analysis. Latent class analysis (LCA) was conducted to identify polysubstance use patterns as well as latent neighborhood constructs. Neighborhood factors included social disorganization, concentrated disadvantage, community resources, community violence, and police station concentration. Multinomial regression analysis was implemented to evaluate the association between polysubstance use class membership and latent classes of neighborhood factors. Result The prevalence of lifetime polysubstance use was 27.56%. Four classes of polysubstance use were identified by comparing a series of five class models. The Bootstrap Likelihood Ratio Test (BLRT) indicated a good fit for the four-class model (<0.001). The prevalence of alcohol latent classes was: (1) heavy alcohol users and experimental smokers (Class I) (15.20%), (2) most hazardous polysubstance users (Class II) (5.33%), (3) heavy smokers and moderate alcohol users (Class III) (7.07%), and (4) experimental alcohol users (Class IV) (72.44%). Three classes of neighborhoods were identified by comparing a series of four-class models. The prevalence of the neighborhood classes was: (1) low social disorganization and disadvantage (Class I) (58.93%), (2) high social disorganization and moderate disadvantage (Class II) (10.93%), and (3) high social disorganization related to perceived drug use and disadvantage (Class III) (30.13%). The BLRT indicated a good fit for the three-class model (p =  < 0.004). Multinomial regression analysis indicated that adolescents living in neighborhoods with high disorder and moderate disadvantage (Class II) were 2.43 times (odds ratio (OR)) = 2.43, confidence interval (CI)) = 1.30–4.56) more likely to be heavy alcohol users and experimental smokers (Class I) compared to experimental alcohol users, adjusting for sex, age, ethnicity, religion, and income. Class II of neighborhood classes presented with the highest levels of community violence (100%), perceived disorder crime (64.6%), police station concentration (6.7%), and community resources (low resources is 87.6%), while the concentrated disadvantage was moderate (14.8%). Conclusions Alcohol polysubstance use latent classes were identified among youth in this context. Neighborhoods with high disorder and moderate disadvantage (Class II) were associated with a higher likelihood of polysubstance use. The role of neighborhood conditions in shaping adolescent polysubstance use should be considered in policy, prevention, and treatment interventions.